Pembangunan Dashboard Inventory Pada Bisnis Ritel - Yusuf Giri Priyangga Adi; Budi Susanto; Maria Nila Anggia Rini (Jurnal Terapan Teknologi Informasi, 2021)
In this study, it will be explained how to create a data mart in a retail business to answer the KPI (Key Performance Indicator) inventory of goods which will be visualized in the form of a dashboard to make it easier for company executives to see the condition of inventory in stores. In making a data mart, it will be explained how the ETL (Extraction, Transformation and Loading) process from a transactional database from 9 stores becomes a data mart. The data mart in this study was built using a star schema and produced 4 dimension tables and 1 fact table. Star schema is used to simplify the query process when you want to display data on the dashboard. After the dashboard has successfully visualized the data, then testing is carried out on users using the UEQ (User Experience Questionnaire) method to find out how the user experience when using the dashboard. From this study, it was found that the dashboard was able to visualize the total inventory of goods, consigned goods inventory, non-consigned trunk inventory in monthly, semester, quarterly, and annual periods. And excellent results on 6 scales of User Experience Questionnaire (UEQ).